Supporting Investments in the Innovative Development of the National Economy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article discusses the problems of investing innovative processes in the national economy of Uzbekistan. In particular, the author analyzed the current state of investment in the innovative development of the national economy, assessed the practice of stimulating innovation and investment activity in Uzbekistan, developed scientific recommendations to increase investment and innovation activity in the sectors of the economy.